(untitled) (Bulletin KNOB, 1996)
The article deals with the dating of a series of Dutch churches by means of dendrochronological research. The exact dates of a number of major monuments could thus be determined. In general one should be cautious when dating towers on the basis of a bell cage found there. Usually these constructions are of a considerably later date. Interesting is the combination of dendrochronological research and a historical record on the Boven- or St. Nicolaas church in Kampen. After the Amsterdam town carpenter, Jan de Jonge, had straightened the strongly subsided tower in 1685, a new, but smaller bell cage was built for one church bell in 1687. Because the tower was subsiding, they did not dare to ring the bells, but now these could be used again without any problem as before, (according to the historical record: ’.....wederom sonder eenige de minste schupel off swarigheijt geluydet en getrocken worden als vanouts’.) Remarkable is the dating of the series of rafters above the central axis of the Nicolai church in Utrecht. On the basis of building-historical and architectural-historical characteristics these roofs were built in the 12th and I3th centuries. However, dendrochronological research proved that the nave dates from 1338, the wood of the rafters reused for the choir from 1345 and the westerly part of the choir from 1365, so considerably later. A possible explanation for the dating of these roofs to the 14th century, in spite of their relatively early characteristics, could be a phased restoration of a highly neglected church, while retaining the old details. Another possibility is renovation after a fire, but the difference between the various building periods would then have been smaller.